FEATURES OF THE LABOR MARKET IN TERMS OF MARKET TRANSFORMATION - Гайдар, О. Є. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2013)
The labor market is an essential and important part of the market economy. The current system of employment in Ukraine is in the crisis state and requires the development of measures to withdraw it from this condition and improve the efficiency of its operation. The article examines the characteristics of employment in the transformation economy in the context of globalization. Basic concepts and essence of employment are considered, the estimation of labor market condition is given.